The Effect Of Problem Based Learning (PBL) Model On Students’ Critical Thinking Ability In The Subject Of Independent Curriculum Of Science In Class IV of SD Inpres Pakkingkingang - Hasmirasari, Hasmirasari; Atjo, Syamsuryani Putri; Raihan, Siti (Program Studi PGSD FIP UNM, 2025)
ResearchThis study aims to determine how the application of the problem-based learning model in the IPAS subject (PBL) model in the IPAS subject, describe students' critical thinking skills in IPAS, and determine the effect of the application of the problem-based learning model in IPAS. in IPAS, and to determine the effect of the application of the problem-based learning model on the critical thinking skills of fourth grade students at SD Inpres Pakkingkingang. The method method used in this research is the Quasi Experimental Design approach with the type of nonequivalent control group design. The population in this study was all students of SD Inpres Pakkingkingang and the research sample was students of class IV B amounted to 15 students class IV A berjumalah 15 students. The sampling technique was purposive sampling. The instruments used were observation sheets and test questions (pretest and posttest) totaling 5 questions (essays).The instruments used were observation sheets and test questions (pretest and posttest) totaling 5 questions (essai). The results of the study, obtained posttest score control class in the good enough category and the experimental class posttest in the very good category which has a positive impact. category which has a positive impact. The results of the inferential analysis obtained P = 0.001 are smaller than α = 0.05 using independent sample t-test, indicating a difference in posttest results between the experimental group and the control group. This shows that the increase in student learning outcomes in the experimental group is better than the control class. This is evidenced by the average value of student posttest results in the experimental group higher than in the control group. So it can be concluded that: (1) the learning process using the problem-based learning model is very good. (2) the test results show an increase in students' critical thinking skills in learning, (3) there is an effect of the problem-based learning model on students' critical thinking skills in the independent curriculum IPAS subject in class IV of SD Inpres Pakkingkingang.